Features of the formation of winter wheat yield depending on the methods of basic tillage and the level of fertilization in the conditions of the southern foothill zone of the North-West Caucasus - N. I. Devterova (Новые технологии)
The research was out on low-humus heavy-duty heavy-clay merged leached chernozems in 2017–2020 in the Republic of Adygea, in the soybeans – winter wheat link of crop rotation. We studied the effect of soil cultivation techniques of varying intensity and fertilization level on the productivity of winter wheat and the agrophysical properties of the soil in its crops. The studies were carried out according to the method of the field experiment by B.A. Dospekhov. It was found that moldboard plowing was a more effective method for cultivating winter wheat, which provided additional formation of +1,18 t/ha (25,7%) of grain in comparison with double disking; sowing of winter wheat provided the maximum yield on the variants with the application of doses of Fon mineral fertilizers (N24 P104 + N5 P20) + N30 + N30, which contributed to the receipt of an additional +0,9 t/ha (18.8%) of grain. The effectiveness of the use of fertilizers for all varieties and doses of fertilizers according to the variants of the experiment was noted. Close correlations between productivity and a set of characteristics: the mass of grain from one spike; the number of grains in an ear; weight of 1000 grains; the total number of plants and productive stems were revealed. The positive effect of plowing on the structural and aggregate composition of the soil was noted. The average indices of the volumetric mass of the cultivated layer by both methods of cultivation did not exceed the optimal values of soil density for the cultivation of winter wheat (1,24–1,27 g/cm3). Productive moisture reserves were assessed as good and satisfactory. It was found that from 51,0 to 88,0% of the yield variability depended on the influence and mutual influence of the most significant elements of the yield structure (R2 is the coefficient of determination 0,88; 0,77; 0,51).